Eage Get 2022 2022
DOI: 10.3997/2214-4609.202221120
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Cyclic Deformation of Sandstones Based on Experimental Observations

Abstract: Underground energy storage (UES) in porous and cavity reservoirs can be used to balance the mismatch between the production and demand of renewable energy. Understanding the geomechanical behaviour of these reservoirs under different storage conditions, i.e., storage frequency and fluid pressure, is key in defining their capacity and effective lifetime. This work presents an analysis performed on sandstones to unravel their geomechanical response under cyclic loading. It includes, importantly, both experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…( 14 ) when . In a recent work 60 , the authors conducted cyclic triaxial experiments on sandstone rock and observed similar trend of the applicability of parameter in sandstone experiments.…”
Section: Inelastic Deformationsmentioning
confidence: 63%
See 1 more Smart Citation
“…( 14 ) when . In a recent work 60 , the authors conducted cyclic triaxial experiments on sandstone rock and observed similar trend of the applicability of parameter in sandstone experiments.…”
Section: Inelastic Deformationsmentioning
confidence: 63%
“…In order to account for cyclic loading effects, we employ the strategy proposed by 59 , in which the equation for the hardening parameter update is properly modified. Recently, cyclic experiments on sandstone have been conducted 60 , where a cyclic MCC model was used to match the experimental results. Finally, the viscoplastic response of shale rock is modeled through Perzyna’s 46 algorithm and the MCC as a yield criterion.…”
Section: Introductionmentioning
confidence: 99%
“…Permanent deformation caused due to triaxial load imposed on the sandstone is modelled using cyclic MCC [167]. Combining hyperelasticity, plastic deformation, and wetting deterioration generalized plastic model was developed [157].…”
Section: Sandstonementioning
confidence: 99%